2018
DOI: 10.1101/333484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural evidence for age-related differences in representational quality and strategic retrieval processes

Abstract: max 170 words)Mounting behavioral evidence suggests that declines in both representational quality and controlled retrieval processes contribute to episodic memory decline with age. The present study sought neural evidence for age-related change in these factors by measuring neural differentiation during encoding of paired associates, and changes in regional BOLD activity and functional connectivity during retrieval conditions that placed low (intact pairs) and high (recombined pairs) demands on controlled ret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…Importantly, the effect of age on reinstatement strength, and the relationship between reinstatement strength and memory performance, was observed after accounting for variance in encoding classifier performance, a putative assay of cortical differentiation (i.e., the ability to establish distinct neural patterns associated with different visual stimulus categories) during memory encoding. Thus, although we found that encoding classifier strength was a strong predictor of reinstatement strength, consistent with prior work (35) and existing proposals regarding dedifferentiation of cortical representations in older adults (5961), the present results suggest that the observed variance in reinstatement strength does not simply reflect downstream effects of cortical differentiation. Instead, variance in reinstatement strength likely also provides information about the precision with which event representations are retrieved in older adults.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Importantly, the effect of age on reinstatement strength, and the relationship between reinstatement strength and memory performance, was observed after accounting for variance in encoding classifier performance, a putative assay of cortical differentiation (i.e., the ability to establish distinct neural patterns associated with different visual stimulus categories) during memory encoding. Thus, although we found that encoding classifier strength was a strong predictor of reinstatement strength, consistent with prior work (35) and existing proposals regarding dedifferentiation of cortical representations in older adults (5961), the present results suggest that the observed variance in reinstatement strength does not simply reflect downstream effects of cortical differentiation. Instead, variance in reinstatement strength likely also provides information about the precision with which event representations are retrieved in older adults.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, it is important to note that variability in episodic remembering, and indeed variability in the strength of the present pattern completion metrics, is likely influenced by a number of variables, only some of which are measured here. For example, aging may affect other processes at retrieval, including elaboration of retrieval cues (63) and post-retrieval monitoring and selection (61, 64), as well as factors at encoding, including the differentiation of stimulus representations (5961), goal-directed or sustained attention (6566), and elaborative or ‘strategic’ encoding processes (6768). These variables could vary both within individuals (i.e., across trials), as well as between individuals (e.g., trait level differences).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, healthy young and older adults encoded words paired with images of faces or scenes as they underwent functional magnetic resonance imaging (fMRI). Face and scene images were selected as stimuli because they have been previously reported to give rise to robust age-related neural dedifferentiation effects (e.g., 24,[26][27][28][29] ). Studied and unstudied words were subsequently presented in a scanned memory test in which, for words judged as studied, a source memory judgment for the corresponding image category was required.…”
Section: Introductionmentioning
confidence: 99%
“…Despite often preserved ability to recognise studied items as previously encountered, and to identify dissimilar novel items as new, older adults are also typically impaired in mnemonic discrimination of studied items from perceptually similar lures (Stark, Yassa, Lacy, & Stark, 2013;Toner, Pirogovsky, Kirwan, & Gilbert, 2009;Yassa et al, 2011), implying a reduced level of detail of the retained memory representations in older age. At the neural level, functional brain imaging has further indicated age-related decreases in the fidelity of neural representations corresponding to different stimuli or task contexts during both encoding and retrieval of episodic memory (Abdulrahman, Fletcher, Bullmore, & Morcom, 2017;St-Laurent, Abdi, Bondad, & Buchsbaum, 2014;Trelle, Henson, & Simons, 2018;Zheng et al, 2018), potentially constraining the precision with which memory representations can be formed as well as recovered in older age.…”
mentioning
confidence: 99%